Indonesian National Interest in South China Sea Conflict Settlement - Beny Abukhaer Tatara; Anastasya Sukma Kundhalini; Bisma Abdurachman; Pujo Widodo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
The issue of the South China Sea conflict as part of the political constellation of the Asia Pacific region has been going on for decades, but until now it has not been resolved even though various settlement efforts have been made by the disputing parties. Although Indonesia is not part of a country that claims territory in the South China Sea (non-claimante state), Indonesia has an interest in efforts to resolve the South China Sea conflict. The purpose of the study is to analyze Indonesia's national interest in efforts to resolve conflicts in the South China Sea. This study uses a qualitative research method with a descriptive approach. Data collection techniques using literature study. The results of the study indicate that Indonesia's national interests in efforts to resolve conflicts in the South China Sea are: Securing national territorial integrity, Securing Economic Resources and protecting the safety of citizens.